1998
DOI: 10.1152/physrev.1998.78.3.583
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin, Thirst, and Sodium Appetite

Abstract: Angiotensin (ANG) II is a powerful and phylogenetically widespread stimulus to thirst and sodium appetite. When it is injected directly into sensitive areas of the brain, it causes an immediate increase in water intake followed by a slower increase in NaCl intake. Drinking is vigorous, highly motivated, and rapidly completed. The amounts of water taken within 15 min or so of injection can exceed what the animal would spontaneously drink in the course of its normal activities over 24 h. The increase in NaCl int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
659
5
24

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 785 publications
(721 citation statements)
references
References 504 publications
33
659
5
24
Order By: Relevance
“…dehydration, hypovolemia, or hyponatremia) (Fitzsimons, 1998). The SFO has been reported to sense circulating Ang II to elicit water-drinking and salt-intake behaviors (Simpson and Routtenberg, 1973).…”
Section: Ii4 Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…dehydration, hypovolemia, or hyponatremia) (Fitzsimons, 1998). The SFO has been reported to sense circulating Ang II to elicit water-drinking and salt-intake behaviors (Simpson and Routtenberg, 1973).…”
Section: Ii4 Discussionmentioning
confidence: 99%
“…Previous studies reported that some neurons in the sCVOs, where AT1a is abundantly expressed, are activated by systemic Na depletion (Fitzsimons, 1998) and that the neural activities in Na-depleted animals are supressed by intracerebroventricular injection of AT1a antagonists along with the reduction of salt-intake behaviors . In the sCVOs, there also exists neurons activated by water depletion (Fitzsimons, 1998), and electrolytic lesions of the sCVOs reduced dipsogenic effects of Ang II (Simpson and Routtenberg, 1975;Lind and Johnson, 1983). These results indicate that the sCVOs are involved in drinking behaviors.…”
Section: Ii1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the injection of angiotensin II into the brain causes significant physiological responses, including increases in blood pressure, drinking behavior, and vasopressin release (45). In addition to the hepatic production of angiotensinogen, it is known to be expressed in astrocytes in the brain (46,47).…”
Section: Brain Functionmentioning
confidence: 99%
“…Il n'est pas du tout impossible que l'action bénéfique de différentes classes d'agents antihypertenseurs puisse être différente entre le jeune hypertendu et la personne âgée lorsque certains segments de l'arbre vasculaire ou lorsque certains organes cibles sont déjà touchés de façon irréversible, pas toujours apparente cliniquement. De nombreuses observations fondamentales et cliniques récentes (intelligence-based medicine) examinent les phénomènes précoces qui caractérisent la maladie hypertensive: la sensibilité au chlorure de sodium [6], la rigidité des gros troncs artériels [7], les anomalies de la perméabilité endothéliale [8], le remodelage précoce vasculaire [9] et extra-vasculaire de la matrice interstitielle [10]. Certaines classes d'antihypertenseurs, tels que les IEC [11], plus récem-ment les antagonistes des récepteurs de l'angiotensine [12], enfin même certains diurétiques [13] ont montré non seulement une action palliative mais encore une action préventive sur les manifestations précoces de la maladie hypertensive.…”
Section: Le Choix Des Patients : Nombreux Mais « âGés »unclassified